Human capital investment: Higher educational and on-the-job training of the marketing practitioner - Johan de W. Bruwer; Norbert E. Haydam (South African Journal of Business Management, 1996)
Human capital theory postulates that investment in people represents an investment in their productive capacity, whether it be in the form of formal educational training or on-the-job training. Today few, if any, occupations require no investment in human capital. An example is marketing practitioners working in the marketing departments of businesses active in the formal sector of the economy. In this empirical research study, the relationship between the formal training that marketing practitioners receive at higher educational institutions and on-the-job training they receive from businesses employing them, are analysed in terms of their job functions and job specifications. Finally, conclusions regarding this specific relationship are made.
Keywords: 650